2012
DOI: 10.1590/s0036-36342012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Iron, zinc, copper and magnesium nutritional status in Mexican children aged 1 to 11 years

Abstract: Objective. To describe the micronutrient nutritional status of a national sample of 1-11 year old Mexican children surveyed in 2006 in National Health and Nutrition Survey (ENSANUT 2006) and their association with dietary and sociodemographic factors. Materials and methods. Serum samples were used (n=5 060) to measure the concentrations of ferritin, transferrin receptor, zinc, copper and magnesium. Results. Prevalence of deficiencies in 1-4 and 5-11y old children were for iron (using low ferritin) 26.0 and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
2
40
0
8
Order By: Relevance
“…24 In Mexico, the prevalence of zinc deficiency varied mildly by age, with rates of 29.2%, 27.5%, and 26.4% for children 1 to 2, 3 to 4, and 5 to 6 years of age, respectively. 26 Mexican and Ecuadorian women 12 to 49 years of age also had high rates of zinc deficiency (28% and 56%, respectively). 24,27 Mexico and Colombia have conducted two consecutive national surveys that collected information on serum zinc concentrations.…”
Section: Prevalence Of Zinc Deficiency In Latin America and The Caribmentioning
confidence: 99%
“…24 In Mexico, the prevalence of zinc deficiency varied mildly by age, with rates of 29.2%, 27.5%, and 26.4% for children 1 to 2, 3 to 4, and 5 to 6 years of age, respectively. 26 Mexican and Ecuadorian women 12 to 49 years of age also had high rates of zinc deficiency (28% and 56%, respectively). 24,27 Mexico and Colombia have conducted two consecutive national surveys that collected information on serum zinc concentrations.…”
Section: Prevalence Of Zinc Deficiency In Latin America and The Caribmentioning
confidence: 99%
“…According to the 2006 National Health and Nutrition Survey in Mexico (relevant to the time in which the study was conducted), the prevalence of low iron stores in 5–11-year-old children nationwide was 13% [10]. In Mexico City, the prevalence of iron deficiency in children 5–11 years old was 4.5%, with a 95% confidence interval (95% CI) between 2.3 and 8.6, and 11% (95% CI: 7.4 – 14.5) in adolescents 12–14 years old [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported such a relationship, e.g., research by Morales-Ruán et al (2012) indicates that as malnutrition becomes more severe in children, ADQ values also decrease. A study by Wang et al (2012) also indicates that nutritional status is associated with ADQ in children.…”
Section: Discussionmentioning
confidence: 76%